Pelatihan Pengelolaan Keuangan Pribadi Yang Baik Bagi Karyawan CV Yuasa Food Untuk Menghadapi Resesi Ekonomi - Eko Sudarso; Bulan Oktrima; Rr Ayu Metarini (Jurnal Abdimas Tri Dharma Manajemen, 2023)
The impact of Covid-19 on the economy and household finances in particular cannot beunderestimated. For this reason, it is important for us to manage our finances well so that ourfinances don't fall apart. This pandemic has changed people's lifestyles. Not only that, thispandemic has also changed the behavior of spending money, such as increased spending ongroceries because people tend to cook for themselves to ensure cleanliness. Spending to buyhealth needs such as vitamins, masks and soap has increased and the cost of telecommunicationdata needed to support Work From Home (WFH) activities has increased. However, there arealso types of expenses that will decrease, such as traveling/vacation funds. The most importantthing at a time like this is to maintain a stable Cash Flow, don't be wasteful and don't buy thingsthat aren't important. We recommend that the extra funds we have save and save into anemergency fund or we can invest it into something profitable. If we apply all of these disciplinesin managing family finances, we will be well prepared to face the economic challenges duringthis pandemic.Keywords: Socialization, Financial Management, Financial Management